The Uniform Law: La nueva normativa jurídica del comercio internacional - Arcos Zapata, Vicente (2009)
The creation of a uniform legal regulation that regulates the different aspects of international trade (Uniform Law) has been a desire of many countries for several decades, a desire driven by globalization and the different processes that it has generated in companies and in the world. international market. This text analyzes not only the importance of the creation of this legal instrument, but also its main characteristics, its range of action and the economic advantages it could bring to trade between nations.